Women's response to the society in Tony Morrison's Novel's, namely Sula, The Bluest Eye and Beloved - Akhter, Nushrat (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2006.